2018
DOI: 10.1038/s41393-018-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive cervical myelopathy had a high risk of developing deep venous thrombosis: a prospective observational study in 289 cases with degenerative cervical spine disease

Abstract: Study design A prospective observational study. Objectives To determine the incidence of deep venous thrombosis (DVT) and to evaluate the risk factors for DVT development associated with degenerative cervical spine disease. Setting Hokkaido Spinal Cord Injury Center, Japan. Methods Between April 2008 and March 2015, patients with degenerative cervical spine disease, such as compressive myelopathy or radiculopathy, who underwent surgical treatment were prospectively assessed. Leg vein ultrasonography and D-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Second, the proportion of surgeries performed among female patients showed an increasing trend over the past 17 years in this study; more female patients than male patients with CDD were admitted for inpatient surgery, and the narrowing gap between the sexes was similar to the results reported in our previous study [45]. Nevertheless, similar to the observations in other studies on cervical diseases, more surgical operations were performed among male patients than among female patients [46][47][48]. There are multiple reasons for this occurrence.…”
Section: Principal Findingssupporting
confidence: 90%
“…Second, the proportion of surgeries performed among female patients showed an increasing trend over the past 17 years in this study; more female patients than male patients with CDD were admitted for inpatient surgery, and the narrowing gap between the sexes was similar to the results reported in our previous study [45]. Nevertheless, similar to the observations in other studies on cervical diseases, more surgical operations were performed among male patients than among female patients [46][47][48]. There are multiple reasons for this occurrence.…”
Section: Principal Findingssupporting
confidence: 90%
“…In this study, we retrospectively analyzed 340 patients and finally found that DVT occurred in 50 patients (14.7%), of which 45 (21.6%) occurred in prone position and five (3.9%) occurred in supine. The overall DVT incidence was relatively high compared with the literature, 1–3,8,26 which may be due to the relatively older age of the cohort with degenerative cervical spine disease, and the fact that no patients received prophylactic anticoagulant therapy preoperatively. An univariate analysis of the collected variables showed that advanced age, preoperative varicose veins in both lower extremities, high D-dimer, high BLV, prolonged operative time, more surgical segments, and surgery in the prone position may act as risk factors for the formation of DVT, which is in line with previous studies 3–6,20,27 …”
Section: Discussionmentioning
confidence: 79%
“…Spinal surgery, personal or family history of VTE, smoking, and diabetes are also risk factors (Piran & Schulman, 2016;Tator et al, 1987;Wei et al, 2023). Individuals with non-traumatic SCL may be similarly at risk for VTE, which can appear before or after surgery (Chung et al, 2011;Yamada et al, 2019).…”
Section: Introductionmentioning
confidence: 99%